An Evaluation of a 1/18o Resolution Regional Ocean Circulation Model of CROCO in the Southern Sunda Shelf - Apriansyah Apriansyah; Agus S. Atmadipoera; Indra Jaya; Dwiyoga Nugroho; Mohd. Fadzil Akhir (Marine Science Department Diponegoro University, 2023)
The Coastal and Regional Ocean Community Model (CROCO) was applied to simulate the three dimensional ocean circulation on the southern Sunda Shelf with a horizontal resolution of 1/18o and 40 vertical layers. This configuration is called as CROCO18-SSS. The initial and open boundary conditions were derived from a global reanalysis product at a resolution of 1/12o from the Copernicus Marine Environment Monitoring Service (CMEMS). The regional model was driven by atmospheric, tides, and river discharges data from a wide variety of datasets, each with a different resolution. To test the model performance and capabilities of the CROCO18-SSS model outputs including sea level anomaly, current velocity, temperature, salinity, and volume transport, we have compared in the simulation results with other reanalysis product and satellite-derived datasets. The CROCO18-SSS model outputs reproduced the regional ocean circulation well from observations and reanalysis products. For example, the reversal of the monsoonal current in the southern sunda shelf, as well as strong persistent southward Makassar throughflow and their interaction in the southern Makassar Strait, can be seen clearly. The vertical structure of the zonal current component was comparable to that of the reanalysis product reference. The seasonal shift in temperature and salinity, with the water becoming colder and saltier during the northwest monsoon and warmer and fresher during the southeast monsoon, was also accurately reproduced by the CROCO18-SSS model. Additionally, the mean volume transport calculated by the CROCO18-SSS model for the Makassar and Karimata Straits was comparable to that reported in previous studies.